How the university ecosystem shapes the innovation capacities of undergraduate students – evidence from Germany. Issue 3 (16th March 2021) - Bock, Carolin; Dilmetz, Daniel; Selznick, Benjamin S.; Zhang, Lini; Mayhew, Matthew J.
ABSTRACT: In society, universities should fulfil their so-called 'third mission' concerning knowledge and technology transfer. However, our knowledge on the impact of the university ecosystem on students' innovative output is still scarce. Our study sheds light on the question whether the university ecosystem stimulates students' innovation capacities or whether innovators are mainly determined by personality traits or family background. The results of our two rounds of surveys, with a total of 345 students of a technical university in Germany, reveal that factors such as functional experiences (e.g. resources and physical spaces within the university) and connecting experiences (e.g. practical application of skills learned during courses) have a significant impact on students' innovation capacities.